Pathway to Hope: an indigenous approach to healing child sexual abuse - Diane Payne; Kimber Olson; Jared W. Parrish (International Journal of Circumpolar Health, 2013)
Background. The Alaska Native (AN) population has endured multiple historical traumatic events. This population has poorer health outcomes on nearly all factors compared with Alaska non-Natives with more than 75% reportedly being physically assaulted in their lifetime, and child sexual abuse nearly 6 times the national average. Objective. This article describes the Pathway to Hope (PTH) program, which is an indigenous approach to ending silence and denial related to child sexual abuse and encourages multigenerational healing. Design. PTH was developed by ANs who believe that each community is unique, thus strategies for ending denial and support for healing must be woven from the historical context, cultural strengths of individual communities. Strengths-based solutions built on truth, honesty, compassion and shared responsibility for healing and protecting today’s children have been profound and successful. The PTH curriculum addresses child sexual abuse from a historical perspective; that the higher rates of sexual abuse among certain Tribes, regions and communities is linked in part to years of victimisation, but may also be perpetuated by internalised oppression and lateral violence among Tribal members. Results. Data suggest that community-based dialogue and wisdom of Native elders and spiritual leaders paired with readiness of community service providers are necessary for sustained change. At all levels, this Indigenous model for learning, sharing, helping and healing brings hope for an end to denial and silence about child sexual abuse for Native people. Conclusions. The PTH program utilises the wisdom and values that have sustained Native people for generations. Ending silence and denial about child sexual abuse and building upon strengths have assisted many Indigenous communities begin the journey toward wellness. Through the PTH, communities have taken steps to accept the challenges associated with establishing safety for children, supporting child victims in healing and to holding offenders ...